The half‐life of political capital: An examination of the temporal effects of board political connections - Hawk, Ashton; Lahiri, Debtanu; Pacheco‐de‐Almeida, Gonçalo (Strategic Management Journal, 2023)
Abstract Research Summary Does corporate political activity (CPA) help sustain performance? Prior literature did not address this question, only whether CPA increases profits—with mixed results over short timescales. We theorize about how political capital affects the regression‐to‐the‐mean of profits through firm and industry persistence mechanisms. Using data on over 6000 firms from 14 democratic countries, we estimate time‐varying, firm‐specific performance persistence coefficients with random‐coefficient models—and profit volatility measures. Triangulating identification methods suggests that the half‐life of political capital is shorter than expected, also compared with other strategy interventions. Political connections are marginally effective at sustaining performance and reducing volatility, delaying profit convergence by only 0.180 years—and with no effect beyond 7 years. Preliminary evidence shows that legislative constraints further curb these modest benefits of CPA. Managerial Summary Corporate political activity (CPA) has an ambiguous impact on firm profits. Yet, it still is a prominent and recurrent firm strategy. Do firms use CPA to sustain existing performance advantages—rather than to create new ones? We show that one type of CPA—the co‐optation of politicians into company boards—does increase the persistence and lowers the volatility of firm performance. However, this effect is surprisingly small: advantages only last 2.4% longer, 7.44 years compared to 7.26 years for politically unconnected firms. Political capital erodes faster than expected, presumably due to political cycles or politically motivated firm strategies that are detrimental to performance. CPA seems less effective at sustaining performance advantages than firm investments in R&D or skilled labor—and has a limited anticompetitive effect.